2014
DOI: 10.4103/0253-7613.135958
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of adenosine diphosphate-induced platelet aggregation by alpha-lipoic acid and dihydroquercetin in vitro

Abstract: Objectives:To investigate the antiplatelet activity of alpha-lipoic acid (α-LA) and dihydroquercetin (DHQ).Materials andMethods: Antiplatelet activity of the α-LA and DHQ was evaluated in rich platelet plasma of rat. The platelet aggregation was induced by adenosine diphosphate (ADP) in concentration of 4 × 10-5 M.Results:α-LA and DHQ inhibited platelet aggregation in concentration-dependent manner. The antiplatelet activity of α-LA was more pronounced than DHQ. DHQ also increased the antiplatelet activity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…These effects may be relevant for the treatment of hypertension and viral infections through improvements in peripheral vascular function and anti-inflammatory activity [ 107 ]. Reported effects on peripheral vascular function and cardioprotective- and anti-inflammatory effects are summarized in Table 8 [ 107 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ]. References to the cellular and molecular mechanisms underlying the biological effects of epicatechin and taxifolin are listed in Table 9 [ 107 , 115 , 119 , 123 , 128 , 130 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 ,…”
Section: The Effects Of Dietary Flavonoids On Microvascular Healthmentioning
confidence: 99%
“…These effects may be relevant for the treatment of hypertension and viral infections through improvements in peripheral vascular function and anti-inflammatory activity [ 107 ]. Reported effects on peripheral vascular function and cardioprotective- and anti-inflammatory effects are summarized in Table 8 [ 107 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 , 123 , 124 , 125 , 126 , 127 , 128 , 129 , 130 , 131 , 132 , 133 , 134 , 135 , 136 , 137 , 138 , 139 ]. References to the cellular and molecular mechanisms underlying the biological effects of epicatechin and taxifolin are listed in Table 9 [ 107 , 115 , 119 , 123 , 128 , 130 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 , 148 , 149 , 150 , 151 ,…”
Section: The Effects Of Dietary Flavonoids On Microvascular Healthmentioning
confidence: 99%
“…Similarly, TX inhibits platelet aggregation induced by ADP and thrombin release [ 95 ]. Kubatiev et al showed that TX causes a concentration-dependent decrease in cytoplasmic Ca 2+ levels in thrombocytes induced by ADP or thrombin probably via the Ca 2+ inhibition channels [ 94 ].…”
Section: Cellular and Molecular Mechanisms Of Ec And Tx Action Relmentioning
confidence: 99%
“…Taxifolin (TAX), a dihydro avonol, is an important natural active ingredient, which has generally been isolated from larch root. In view of its structure containing more phenolic hydroxyl groups, TAX has a variety of biological activities, including anti-in ammatory, antioxidant, anti-proliferation and antianaphylaxis effects (Kim et al 2008;Ahn et al 2010;Ivanov et al 2014) Therefore, TAX has high development potential, such as food additives, health foods and medicines. TAX was rst extracted from Douglas r bark by Japanese scholars using hot water extraction (Fukui et al 1966).…”
Section: Introductionmentioning
confidence: 99%